Slaxx [videorecording (DVD)] - Kephart, Elza, 1976-; Gomez Zlatar, Patricia; Denis, Romane; Donahue, Brett, 1986-; Bhojani, Sehar; Bogaert, Stephen; Measroch, Delphine; Asselin, Steve (RLJE Films, Shudder, 2021)
A possessed pair of jeans is brought to life to punish the unscrupulous practices of a trendy clothing company. Shipped to the company's flagship store, the killer jeans proceed to wreak carnage on staff who are locked in overnight to set up the new collection.